Mothers Who Engage in Long-Term Informal Milk Sharing. Issue 6 (November 2020) - McNally, Deirdre; Spatz, Diane L.
Abstract : Abstract: Human milk has repeatedly been shown to be the best form of infant nutrition. Many reasons may prevent a family from providing human milk to their child, leaving them to seek other options. One alternative is informal milk sharing, where individuals and families find donor milk through online communities. We present perspectives from three mothers who used informal milk sharing for at least 6 months. Common themes identified are sadness, guilt, and stigmatization of informal milk sharing. Implications for practice include providing families and practitioners with resources for learning about informal milk sharing and navigating the community safely. Abstract : When some new mothers are unable to breastfeed, they seek human milk through informal sources, usually located on line. Three new mothers who obtained human milk for their babies via informal milk sharing networks offer insight into their experiences. Suggestions for helping nurses, midwives, physicians, and other health care providers become more familiar with this process and offer support to their patients are included.